Similar neural pathways link psychological stress and brain-age in health and multiple sclerosis - Marc-Andre Schulz; Stefan Hetzer; Fabian Eitel; Susanna Asseyer; Lil Meyer-Arndt; Tanja Schmitz-Hübsch; Judith Bellmann-Strobl; James H. Cole; Stefan M. Gold; Friedemann Paul; Kerstin Ritter; Martin Weygandt (iScience, 2023)
Summary: Clinical and neuroscientific studies suggest a link between psychological stress and reduced brain health in health and neurological disease but it is unclear whether mediating pathways are similar. Consequently, we applied an arterial-spin-labeling MRI stress task in 42 healthy persons and 56 with multiple sclerosis, and investigated regional neural stress responses, associations between functional connectivity of stress-responsive regions and the brain-age prediction error, a highly sensitive machine learning brain health biomarker, and regional brain-age constituents in both groups. Stress responsivity did not differ between groups. Although elevated brain-age prediction errors indicated worse brain health in patients, anterior insula–occipital cortex (healthy persons: occipital pole; patients: fusiform gyrus) functional connectivity correlated with brain-age prediction errors in both groups. Finally, also gray matter contributed similarly to regional brain-age across groups. These findings might suggest a common stress–brain health pathway whose impact is amplified in multiple sclerosis by disease-specific vulnerability factors.